Impact of employer-employee relationship towards employee's performance / Tenni Asun and Erme Surianie Poyok - Asun, Tenni; Poyok, Erme Surianie (2016)
The aim of this study was to analyse the impact of employer-employee relationship in the organization towards employees' performance and to determine the correlation between employer-employee relationships with employees' work performance. In this study, there were 221 of employee work around Sepanggar involved as respondent of this study. There were three impact of employer-employee relationship in the organization towards employees' performance that includes motivation, attendance to work and less conflict. The result show that there is correlation between employer-employee relationships with employees; work performance.